The acquisition of the locative subject construction in Mandarin: An aspectual account - Deng, Xiangjun (Lingua, 2020)
•Mandarin locative subject sentences (LSSs) only allow (derived) State verbs.•Aspectually marked LSSs are extremely rare in preschooler's speech.•Children showed low sensitivity to LSSs’ aspectual properties in the experiment.•Late acquisition caused by insufficient input, and the construction's complexity. Mandarin locative subject construction involves mismatches across argument structure and information structure, as well as complex interactions between event types and aspect markers. Acquiring the construction requires the integration of information across syntax–pragmatics and syntax–semantics interfaces, and thus it is predicted to be difficult. Based on the data of 151 children from age 1;7 (one year and seven months) to 6;0 (six years) in three child Mandarin corpora, we found that locative subject sentences (LSSs) emerged around 2;0, but the early verbs are exclusively existential verbs. Aspectually marked LSSs are extremely rare in child data, with only a few having placement verbs and posture verbs marked with the perfective aspect marker -le. In our modified forced-choice experiment, the children showed low sensitivity to this construction's aspectual properties: three-year-olds significantly differed from adults in rejecting aspectually marked LSSs; up to six years old, the children could not identify the aspectual clash between a manner-of-motion verb and -le, and the clash between a transitive process verb and Agent. Such low sensitivity is attributed to Mandarin-speaking children's insufficient exposure to aspectually marked LSSs in the input as shown by our corpus data and the complexity posed by the interface properties of this construction.